2017
DOI: 10.1021/acsomega.7b00563
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polyethylene Fibers of Very High Thermal Conductivity Enabled by Amorphous Restructuring

Abstract: High-thermal-conductivity polymers are very sought after for applications in various thermal management systems. Although improving crystallinity is a common way for increasing the thermal conductivity ( k ) of polymers, it has very limited capacity when the crystallinity is already high. In this work, by heat-stretching a highly crystalline microfiber, a significant k enhancement is observed. More interestingly, it coincides with a reduction in crystallinity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…4(b). The thermal conductivity of a thermally stretched UHMW-PE microfiber approaches 51 W·m -1 ·K -1 , while its crystallinity is reduced from 92% to 83% during the stretching [20]. Such increased thermal conductivity is due to the improved chain alignment in the amorphous domains.…”
Section: Mechanical Stretchingmentioning
confidence: 98%
See 1 more Smart Citation
“…4(b). The thermal conductivity of a thermally stretched UHMW-PE microfiber approaches 51 W·m -1 ·K -1 , while its crystallinity is reduced from 92% to 83% during the stretching [20]. Such increased thermal conductivity is due to the improved chain alignment in the amorphous domains.…”
Section: Mechanical Stretchingmentioning
confidence: 98%
“…Copyright 2010 Nature Publishing Group; (b) influence of crystalline in UHMW-PE. [20] Copyright 2017 American Chemical Society; (c) Tensile effects on thermal transport in carbine and cumulene [23]. copyright 2015 Nature Publishing Group.…”
Section: Mechanical Stretchingmentioning
confidence: 99%
“…It was reported that the armchair and zigzag thermal conductivities were 23-33 and 73-93 W m À1 K À1 , respectively. 16 There are other techniques that can be used for studying the anisotropic thermal conductivity of BP, such as the modified laser-flash technique, 19 pulsed laser-assisted thermal relaxation technique, 20 transient electro-thermal technique, [21][22][23][24] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a resulting (010) peak was also found in UHMWPE fibers after hot drawing process. [43] This peak indicates that monoclinic/triclinic crystals have emerged and coexist with the dominant orthorhombic form.…”
Section: Morphologymentioning
confidence: 99%